2016
DOI: 10.1097/bpb.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage medial open reduction and Pemberton acetabuloplasty in developmental dysplasia of the hip

Abstract: In this study, we aimed to evaluate the long-term clinical and radiological results of single-stage open reduction through a medial approach and Pemberton acetabuloplasty in developmental dysplasia of the hip. We treated 32 hips (22 patients) with developmental dysplasia by a single-stage open reduction through Ferguson’s medial approach and Pemberton acetabuloplasty. The procedure was performed bilaterally in 10 patients. The mean age of the patients at the time of the operation was 19.8 months (16–24 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…Table 3 shows the retrieved articles, population characteristics and the surgical strategy. 17,23,27 –71…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the retrieved articles, population characteristics and the surgical strategy. 17,23,27 –71…”
Section: Resultsmentioning
confidence: 99%
“…Baki et al also used the Severin classification in their study to analyze the radiological results of patients who underwent the posteromedial limited approach and Pemberton osteotomy. Only 1 of the 22 patients was a male 13 . In their study of mid-term radiological results after the posteromedial limited approach, Biçimoğlu et al concluded that sex does not make a difference in terms of radiological results.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that female sex is a risk factor for DDH, its effects on prognosis are unclear. In the current literature, male and female patients were studied together, and male patients constituted only a small part of the cohorts 13, 14. To the best of our knowledge, this is the first study comparing male and female patients based on the mid-long-term results of the posteromedial limited approach.…”
Section: Discussionmentioning
confidence: 99%
“…La corrección de la DDC en pacientes de edad ambulatoria tiene diferentes tipos de tratamiento quirúrgico, algunas de estas opciones van desde la colocación de una tracción pre o transoperatoria para facilitar la reducción de la cadera y disminuir el riesgo de necrosis avascular, 17 otra opción quirúrgica es una cirugía de un solo paso, pero con la variante de una reducción abierta a través de un abordaje medial, seguido de una osteotomía de Pemberton por vía anterior. 18 En este estudio se evaluó una técnica integral de un solo paso para realizar la corrección completa de las deformidades óseas y las alteraciones de los tejidos blandos de la cadera.…”
Section: Discussionunclassified